Winning Customers through Service Innovation-CAB WISE - Nagu, Vinay Kumar (Indian Journal of Marketing, 2010)
Meru Cabs, operating in four major cities of the country has known and introduced the concept of radio cabs. It has initiated a slew of strategies and invested considerable sums in brand building. A great number of passengers who avail taxi services today have Meru at the top of their mind. By making the ’taxi’ experience more comfortable, safe and reliable in India, Meru has been in a position to obtain rich dividends. In a matter of two years, Meru Cabs has captured the market by storm. However, competition is growing and there is every need for Meru to protect and enhance its market share. In the paper, we outline some strategies to help Meru keep competitors at bay. The company started in a small way in 1998, when Neeraj Gupta started off with a small auto workshop, ’Elite Class’ to provide high quality auto maintenance services at affordable prices. The unprecedented success of ’Elite Class’ with corporate clients such as Tata Infotech, Blue Dart and Sony, led Gupta to start a passenger transport business under the name ’Travel Link’ in 2002. Within a year, the sales increased by a factor of eight. In 2004, Travel Link was rechristened ’V-Link Tours & Travels’. In partnership with private equity firm India Value Fund Advisors, Meru Cabs metered taxi services was launched. The company received an offer letter from Maharashtra government to operate the radio taxis in Mumbai. Initially, the service was limited to Mumbai Metropolitan Region (MMR), but by June 2007, the service started covering the entire city with an increased fleet size. Starting off with mere 46 cabs, the company was successful in registering about 200 cabs within three months of operations. It is common knowledge that the company faced stiff opposition from the conventional black and yellow taxis of Mumbai. The company later made a specific network of business and leisure travelers, thus creating its own brand in the market. Today, it has redefined transport sector backed with 24X7 call centre and with its trained staff of professional drivers (called subscribers by Meru). Gupta even received the Udyog Rattan Award from The Institute of Economic Studies for the high quality of transport services offered by the company.